Analisis Faktor-Faktor yang Mempengaruhi Strutur Modal Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2017-2021 - Richo Yahya Effendi; Bambang Sudarsono (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This study aims to determine what factors influence the capital structure of the sub-sector of manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. As is well known, the capital structure contained in the company can be measured using several variables that are in accordance with this study, namely by using the ROE, company size (Ln of Total Assets) and profitability (ROA) variables. The subjects of this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The companies used as samples in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period which publish their financial statements every year. This study is a quantitative study with data sourced from the company's financial statements published on the Indonesia Stock Exchange. The results showed the effect of ROE, Firm Size (Ln of Total Assets) and ROA partially and simultaneously on the capital structure. The results of this study are useful for knowing more about the effect of ROE, Firm Size (Ln of Total Assets) and ROA partially and simultaneously on capital structure.